Study of the state of th vascular endothelium in various forms of coronary heart disease - F. A. Shukurov; M. S. Tabarov; Z. M. Toshtemirova; M. Kh. Khodzhaeva (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье, 2023)
Purpose of the study: to investigate changes in markers of endothelial dysfunction and hemostasis system in patients with different forms of CHD on the background of treatment and before it.Materials and methods of the study. In order to fulfill the set tasks, 60 patients with different forms of CHD: stenocardia and myocardial infarction (according to the classification of the Canadian Association of Cardiology (L. Cam-peau, 1976)), 60 patients with different forms of CHD were examined during the study. Campeau, 1976), VNOC (2004), recommendations of the European Society of Cardiology (2007)), aged from 50 to 75 years (mean age 62.6 ± 3.5 and 65.1 ± 3.6 years, respectively) and 20 practically healthy individuals (without signs of CHD), comparable in age (mean age 62.7 ± 3.7 years), who constituted the control group. For comparative analysis of the results before and after treatment the subjects were divided into three groups: Group I - control group, respondents without CHD; Group II - patients with stable angina II and III functional classes (FC); Group III - patients with postinfarction cardiosclerosis, i.e. those who had undergone Ml.Results and their discussion Several risk factors were identified in the majority of hospitalized patients. CHD of II and III FC was more often registered in women (60%); men who had undergone myocardial infarction accounted for 63.3%, the indices were statistically insignificant (p >0.05). The main cardiovascular risk factors (obesity, arterial hypertension, body mass index and total cholesterol) were significantly higher (in % ratio) in patients of groups ll-lll compared to group I (p<0.001), but the cholesterol content and body mass index were on average higher in group II (4.5 ± 1.0 and 33.0 ± 1.3, respectively) than in group III (4.2 ±1.1 and 30.6 ± 2.6, respectively). As for the duration of the disease, group III patients were characterized by a longer history and a higher frequency of heart failure, i.e. patients in this group had a more severe clinical status (p > 0.05). It should be noted that of the total number of patients (n = 80), rural residents accounted for 46.25% and city dwellers for 53.75%.ConclusionsThe presence of a higher degree of endothelial dysfunction is observed in patients who underwent myocardial infarction, in contrast to the stable form of angina pectoris without myocardial infarction in the anamnesis. The progression and deterioration of vascular endothelium is mostly associated with the presence of hyperhomocysteinemia, and the most pronounced changes in endothelial function are determined in patients with a combination of cardiovascular risk factors. In different forms of CHD the increased content of DEK and homocysteine in blood serum, increasing in parallel with the severity of clinical course, their level correlates with the degree of endothelial dysfunction. A direct correlation between hemostasis markers (von-Willebrand factor, fibrinogen and platelets) and DEK was revealed. The greatest changes in vascular-thrombocytic and coagulation hemostasis are observed in patients with IMI than in patients with stenocardia.